The study of lipid profile, diet and other cardiovascular risk factors in children born to parents having premature ischemic heart disease - M R Savitha; B Sandeep (Wolters Kluwer Medknow Publications, 2011)
Background: Dyslipidemia is a marker for ischemic heart disease (IHD), which can be detected in early childhood and tracks to adulthood. Dyslipidemia, along with factors like diet, obesity and sedentary activity, increases the risk of a child developing IHD in adulthood. Early detection and modification of these risk factors can prevent IHD. Objectives: To study the lipid profile in children born to parents with history of premature IHD and also to study the effect of diet, lifestyle factors, and obesity in the study group. Materials and Methods: Fifty children of parents with premature IHD and 50 control children without any family history of IHD were analyzed for cardiovascular risk factors such as lipid profile, body mass index (BMI) and hypertension. The effects of modifiable risk factors like diet and physical activity on lipid profile were analyzed. The correlation between parent and child lipid profile was studied. Results: Mean total cholesterol, low density lipoprotein cholesterol and triglycerides were significantly higher (P<0.05) in children with family history of IHD as compared to children without family history. There was a positive correlation between lipid levels of parents and their children. Children with elevated BMI, a sedentary lifestyle, and excess oily/junk diet intake showed increased incidence of dyslipidemia (P<0.05). Conclusions: Children of IHD patients have significant incidence of dyslipidemia. The risk factors like BMI, diet and physical activity increase the incidence of dyslipidemia. Therefore, all children of premature IHD patients should be screened for dyslipidemia.